Analysis and Design of Digital IIR Integrators and Differentiators Using Minimax and Pole, Zero, and Constant Optimization Methods. (6th June 2013) - Jain, Madhu; Gupta, Maneesha; Jain, N. K.
Abstract : Proposed work deals with the design of a family of stable IIR digital integrators via use of minimax and pole, zero, and constant optimization methods. First the minimax optimization method is used to design a family of second-, third-, and fourth-order digital integrators by optimizing the magnitude response in a min-max sense under the satisfactory condition of constant group delay. Then the magnitude and group delay response is further improved using pole, zero, and constant optimization method. Subsequently, by modifying the transfer function of all of the designed integrators appropriately, new differentiators are obtained. Simulation results show that proposed approach outperforms existing design methods in terms of both magnitude and phase response.